Crypsis in two species of tinamou (Tinamiformes: Tinamidae): roosting Solitary Tinamous [Tinamus solitarius (Vieillot, 1819)] probably mimic owls - Smith, Paul; Morris, Pete (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
Observations of defensive behaviours in two species of tinamous are described. Use of the subcaudal feathers as a means of nest crypsis is described and illustrated in an incubating Tataupa Tinamou (Crypturellus tataupa (Temminck, 1815)). An arboreal roosting Solitary Tinamou (Tinamus solitarius (Vieillot, 1819)) is shown to deliberately assume a tail up posture indicating Batesian mimicry of a large owl. It is hypothesised that the imbricated scales on the posterior tarsi of this species assist in assuming this posture, and that such a defence is necessary given the exposed perches on which they choose to roost and the notoriously poor flight capacity of members of this family.